The gender unemployment gap - Stefania Albanesi; Ayşegül Şahin (Federal Reserve Bank of New York, 2013)
The unemployment gender gap, defined as the difference between female and male unemployment rates, was positive until 1980. This gap virtually disappeared after 1980 - except during recessions, when men's unemployment rates always exceed women's. We study the evolution of these gender differences in unemployment from a long-run perspective and over the business cycle. Using a calibrated three-state search model of the labor market, we show that the rise in female labor force attachment and the decline in male attachment can mostly account for the closing of the gender unemployment gap. Evidence from nineteen OECD (Organisation for Economic Co-operation and Development) countries also supports the notion that convergence in attachment is associated with a decline in the gender unemployment gap. At the cyclical frequency, we find that gender differences in industry composition are important in recessions, especially the most recent, but they do not explain gender differences in employment growth during recoveries.
Keywords: E24; J64; 330; Arbeitslosigkeit; Geschlecht; Weibliche Arbeitskräfte; USA